Tepotinib for the Treatment of Lung Adenocarcinoma Harboring MET Y1003N Point Mutation: A Case Report - Yukihiro Umeda; Satomi Kimura; Junya Kimura; Yoshiaki Imamura; Tamotsu Ishizuka (Thoracic Cancer)
ABSTRACT The mesenchymal‐epithelial transition factor (MET) Y1003 mutation, like MET ex14 skipping, is an oncogenic driver mutation that suppresses MET degradation. Herein, we report the case of a 63‐year‐old female patient with lung adenocarcinoma harboring the MET Y1003N mutation, who was treated with tepotinib, a selective type 1b MET tyrosine kinase inhibitor. To the best of our knowledge, no such cases have been reported. The woman was referred to our hospital with the chief complaint of chest pain. After a detailed examination, she was diagnosed with stage IVB lung adenocarcinoma. Next‐generation sequencing revealed an MET Y1003N mutation in the tumor. Tepotinib was administered as the eighth‐line treatment, and the best overall response was a partial response that lasted for 8 months. In lung adenocarcinomas harboring the MET Y1003 mutation, selective type 1b MET tyrosine kinase inhibitors may be an important treatment option, even in heavily pretreated settings.